2021
DOI: 10.3390/children8070591
|View full text |Cite
|
Sign up to set email alerts
|

Achievement Goals, Fear of Failure and Self-Handicapping in Young Elite Athletes with and without Chronic Pain

Abstract: Background: Pain is a common problem in elite athletes. This exploratory study compares goal orientations towards sport, fear of failure, self-handicapping and pain catastrophizing between active young elite athletes with and without chronic pain (CP) complaints (longer than three months). It examines the associations between chronic pain, fear of failure, goal orientations, self-handicapping and pain catastrophizing in young elite athletes. We explore how far goal orientation can be explained by these factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
6
2
0
Order By: Relevance
“…Students who fear or avoid appearing incompetent engage in an SH strategy. This study supports the findings of previous researchers who stated that SH is a strategy to manage self-image associated with feelings of fear of failure (e.g., De Castella et al, 2013;Lee et al, 2021;Merolla & Jackson, 2019;Molenaar et al, 2021). Both BSH and CSH are ways to avoid failure or feelings of fear of failure.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Students who fear or avoid appearing incompetent engage in an SH strategy. This study supports the findings of previous researchers who stated that SH is a strategy to manage self-image associated with feelings of fear of failure (e.g., De Castella et al, 2013;Lee et al, 2021;Merolla & Jackson, 2019;Molenaar et al, 2021). Both BSH and CSH are ways to avoid failure or feelings of fear of failure.…”
Section: Discussionsupporting
confidence: 90%
“…This study reinforces the results of previous research that the role of PApG in learning activities is less clear (e.g., Hoffman et al, 2019;Lee et al, 2016). Several previous studies found a negative relationship between PApG and SH (e.g., Akin, 2014;Lee et al, 2021;Schwinger et al, 2014), and some other studies the two were positively related (e.g., Molenaar et al, 2021;Sameer Babu & Selvamari, 2018) The results of this study also strengthen the results of previous studies that MApG has a significant negative relationship both with BSH and CSH (e.g., Akin, 2014;Martin et al, 2015;Schwinger et al, 2014). Individuals who pursue mastery of learning materials view failure as part of the learning process, so failure is not something to be afraid of.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Along these lines, Conroy et al (2001) and Conroy et al (2002) perform in‐depth interviews to shed light on the nature of the cognitive‐motivational‐relational appraisals associated with fear of failure in elite athletes. Similarly, Gómez‐López et al (2020), Molenaar et al (2021), Thuany et al (2022) among others, show a negative relationship between sports competition and performance.…”
Section: Brief Review Of the Literaturementioning
confidence: 85%
“…Thus, both hope for power and fear of losing power could lead to a performance-avoidance goal. Therefore, fear of failure [13] and both variables of power motive (hope for power and fear of losing power) [10] [14] should be minimized to prevent the tendency to the selection of performance-avoidance goal orientation.…”
Section: Introductionmentioning
confidence: 99%